A review on LED technology in water photodisinfection - Martín-Sómer, Miguel; Pablos, Cristina; Adán, Cristina; van Grieken, Rafael; Marugán, Javier (The Science of the total environment, 2023)
The increase in efficiency achieved by UV LED devices has led to a compelling increase in research reports on UV LED water treatment for consumption in the past few years. This paper presents an in-depth review based on recent studies on the suitability and performance of UV LED-driven processes for water disinfection. The effect of different UV wavelengths and their combinations was analysed for the inactivation of various microorganisms and the inhibition of repair mechanisms. Whereas 265 nm UVC LED present a higher DNA damaging potential, 280 nm radiation is reported to repress photoreactivation and dark repair. No synergistic effects have been proved to exist when coupling UVB + UVC whereas sequential UVA-UVC radiation seemed to enhance inactivation. Benefits of pulsed over continuous radiation in terms of germicidal effects and energy consumption were also analysed, but with inconclusive results. However, pulsed radiation may be promising for improving thermal management. As a challenge, the use of UV LED sources introduces significant inhomogeneities in the light distribution, pushing for the development of adequate simulation methods to ensure that the minimum target dose required for the target microbes is achieved. Concerning energy consumption, selecting the optimal wavelength of the UV LED needs a compromise between the quantum efficiency of the process and the electricity-to-photon conversion. The expected development of the UV LED industry in the next few years points to UVC LED as a promising technology for water disinfection at a large scale that could be competitive in the market in the near future. [Display omitted] •265 nm wavelength have higher germicidal effect, but 280 nm represses cell repair.•280 nm LED have higher electricity-to-photon conversion compared to 265 nm LED.•UVA exposure before UVC affects biological processes in bacterial inactivation.•Pulsed UVC LED does not affect activity but improves temperature control.•Expected deployment of UVC LED in the upcoming future in water disinfection